Sulfate triple-oxygen-isotope evidence confirming oceanic oxygenation 570 million years ago - Haiyang Wang; Yongbo Peng; Chao Li; Xiaobin Cao; Meng Cheng; Huiming Bao (Nature Communications, 2023)
Abstract The largest negative inorganic carbon isotope excursion in Earth’s history, namely the Ediacaran Shuram Excursion (SE), closely followed by early animal radiation, has been widely interpreted as a consequence of oceanic oxidation. However, the primary nature of the signature, source of oxidants, and tempo of the event remain contested. Here, we show that carbonate-associated sulfate (CAS) from three different paleocontinents all have conspicuous negative 17O anomalies (Δ′17OCAS values down to −0.53‰) during the SE. Furthermore, the Δ′17OCAS varies in correlation with its corresponding δ34SCAS and δ18OCAS as well as the carbonate δ13Ccarb, decreasing initially followed by a recovery over the ~7-Myr SE duration. In a box-model examination, we argue for a period of sustained water-column ventilation and consequently enhanced sulfur oxidation in the SE ocean. Our findings reveal a direct involvement of mass-anomalously 17O-depleted atmospheric O2 in marine sulfate formation and thus a primary global oceanic oxygenation event during the SE.